2006
DOI: 10.1007/s00402-006-0154-1
|View full text |Cite
|
Sign up to set email alerts
|

The SLAP lesion as a reason for glenolabral cysts: a report of five cases and review of the literature

Abstract: Our results are based on the assumption that cysts in the region of the spinoglenoidal/supraglenoidal incisura can originate from SLAP lesions. If a patient is suspected of having cysts in this region, the question of a SLAP lesion should be clarified. SLAP lesions should be repaired to avoid relapse. Arthroscopic repair of SLAP lesion can lead to the disappearance of symptoms in younger patients. In older patients puncture or resection of the ganglion alone may be an adequate therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…4,5 On the other hand, cysts may reform after simple removal or aspiration when the labrum is not repaired. 1,3,4,8 Given the primary presentation of a painless, enlarging neck mass with minimal shoulder symptoms, no shoulder trauma, and a normal shoulder exam, a ganglion cyst of the neck should result in consideration of a SLAP lesion of the shoulder. In this case, the shoulder MRI was of critical importance to direct the surgical management to include arthroscopic repair of the primary lesion in the shoulder, in addition to the excision of the neck mass.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 On the other hand, cysts may reform after simple removal or aspiration when the labrum is not repaired. 1,3,4,8 Given the primary presentation of a painless, enlarging neck mass with minimal shoulder symptoms, no shoulder trauma, and a normal shoulder exam, a ganglion cyst of the neck should result in consideration of a SLAP lesion of the shoulder. In this case, the shoulder MRI was of critical importance to direct the surgical management to include arthroscopic repair of the primary lesion in the shoulder, in addition to the excision of the neck mass.…”
Section: Discussionmentioning
confidence: 98%
“…Without labral repair, cyst formation often recurs [11,13,17,18,20]. Previous studies have established the pathophysiology and recommended a treatment algorithm for treatment of this condition [8,13]. These studies recommend an initial trial of nonoperative management for patients with weakness and spinoglenoid notch cysts followed by arthroscopic cyst decompression and repair of SLAP (superior labral anterior posterior) lesions if the patients are still symptomatic, although the duration of nonoperative treatment was not specified.…”
Section: Introductionmentioning
confidence: 95%
“…[6][7][8]17,18,21,23,26,27,39,40 Several authors have shown that it is possible to treat this condition by repairing the coexistent labral pathology, without the need to perform an open or arthroscopic decompression or a resection of the cyst. 23,26,40 Previously, an open approach was employed to treat intraneural ganglion cysts of the SSN by resecting the articular branch and decompressing or resecting the cyst.…”
mentioning
confidence: 99%